Sequential laxative-probiotic usage for treatment of irritable bowel syndrome: a novel method inspired by mathematical modelling of the microbiome - Li, Ming; Xu, Ri; Li, Yan-qing (Scientific reports, 2020)
The gut microbiome plays an important role in human health. However, its response to external intervention is complex. A previous study showed that the response to Clostridium butyricum (CB) treatment of irritable bowel syndrome (IBS) is heterogeneous. We proposed that mathematical model simulation of the microbiota may help to optimize the management of IBS-associated microbiota. In this study, a novel mathematical non-extinction and defecation normalized (NEDN) model was generated for stable simulation of the dynamic nature of gut microbiota. In silico simulation revealed that a laxative may create a favourable opportunity for Clostridium cluster XIVa to shift the microbiota. An explorative clinical trial was conducted to compare three CB regimens in an IBS cohort: laxative, interval of 2 weeks and CB administration for 2 weeks (L2P); laxative immediately followed by CB administration (LP) for 2 weeks; and CB administration for 2 weeks (P). The LP regimen optimally relieved the IBS symptoms and shifted the microbiota closer to those of the healthy subjects during 2 weeks of CB intake. These results indicate that integration of biological/mathematical approaches and clinical scenarios is a promising method for management of microbiota. Additionally, the optimal effect of sequential laxative-CB usage for IBS treatment warrants further validation. Clinical trial registration numbers: NCT02254629. Date of registration: October 2, 2014.